2018
DOI: 10.1111/ecc.12980
|View full text |Cite
|
Sign up to set email alerts
|

Does age matter? A comparison of health-related quality of life issues of adolescents and young adults with cancer

Abstract: Objective Health‐related quality of life (HRQoL) concerns of adolescents and young adults (AYAs) aged 14–25 years were compared with those of older adults (26–60 years) with cancer. Methods AYAs and older adults receiving curative intent treatment or supportive palliative care for cancer were recruited from eight research centres across Europe. Participants used a rating scale to score the relevance and importance of a list of 77 issues covering 10 areas of HRQoL concern: symptoms; activity restrictions; socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…[3][4][5][6] Cancer can be especially disruptive to education and employment opportunities for AYA patients. 3,[7][8][9] This interruption in their developing lives can lead adolescent patients with cancer to feel a longing for normalcy, especially as they observe friends pursuing and achieving goals that they cannot attain. 10,11 Similarly, cancer causes many financial setbacks for AYA patients.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Cancer can be especially disruptive to education and employment opportunities for AYA patients. 3,[7][8][9] This interruption in their developing lives can lead adolescent patients with cancer to feel a longing for normalcy, especially as they observe friends pursuing and achieving goals that they cannot attain. 10,11 Similarly, cancer causes many financial setbacks for AYA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Full paper studies reported in English and published in 2000 or later were included if: (1) the objective was to describe HRQoL of patients with sarcoma; (2) patients had an age at sarcoma diagnosis of ≥15 years, as previous research has shown that patient-reported outcome measures (PROMs) that were developed for adults are applicable to adolescents and young adults(AYAs). 20 …”
Section: Methodsmentioning
confidence: 99%
“…Full paper studies reported in English and published in 2000 or later were included if: (1) the objective was to describe HRQoL of patients with sarcoma; (2) patients had an age at sarcoma diagnosis of ≥15 years, as previous research has shown that patient-reported outcome measures (PROMs) that were developed for adults are applicable to adolescents and young adults(AYAs). 20 Studies were excluded: (1) if they presented data of a study sample that included patients with gastrointestinal stromal tumours, desmoid-type fibromatosis, giant cell tumours, tenosynovial giant cell tumour formerly known as pigmented villonodular synovitis, Kaposi sarcoma, carcinosarcoma or benign bone or soft tissue lesions that comprised >20% of the total population; (2) if the study sample consisted of multiple cancer types including sarcoma but the HRQoL outcomes for patients with sarcoma could not be extracted; (3) if they presented data of fewer than 10 patients with sarcoma and (4) if they presented physician-reported outcome data (eg, Musculoskeletal Tumour Society Score). The described selection criteria were applied to the hits.…”
Section: Selection Criteriamentioning
confidence: 99%
“…For example Specific barriers to AYA entering clinical trials are now characterised (Fern, Lewandowski, Coxon, & Whelan, ) Patient and health service organisational factors that underpin advanced disease at AYA cancer presentation are increasingly understood (Herbert et al, ) Biological differences between apparently similar cancers in AYA and other age groups are described in some areas (Tricoli et al, ) The specific healthcare professional competencies required for working with AYA are characterised (Taylor et al, ) The social difficulties of AYA with cancer are specifically and systematically described (Warner et al, ). The unmet needs of AYA have been frequently described and differ relatively little during the cancer trajectory (Lea et al, ). In this edition, Darlington et al comprehensively describe how specific AYA needs can influence the quality of life (Sodergren et al, ). …”
Section: We Should Design and Implement Intervention Studies In Our Pmentioning
confidence: 99%
“…In this edition, Sodergren et al comprehensively describe how specific AYA needs can influence the quality of life (Sodergren et al, 2018).…”
Section: We S Hould De S I G N and Implement Interventi On S Tud Iementioning
confidence: 99%